Associaton of estrogen receptor, progesterone receptor and c-erbb2 receptor expression in invasive ductal carcinoma of breast Serdang Hospital from 2010 to 2012 - Nurain Adnan
Background:Carcinoma of breast is the most common malignancy in woman worldwide and the second most common cause that leads to cancer mortality. Estrogen receptor (ER), progesterone receptor (PR), and c-erbB2 (HER2/neu) are therapeutically and prognostically imp0I1ant markers in the management nfbreast carcinoma. Objectives: The objectives of this study is to determine the association of estrogen.progesterone, and C-erbB2 receptor expression in invasive ductal carcinoma of breast based on patient" s age group. ethnicity and tumour histological grade. Methods: A hospital-based cross-sectional study was conducted by assessing laboratory data of Infiltrating Ductal of Carcinoma of breast for January 2010 to December 2012 through universal sampling in Histopathology Laboratory of Pathology Depm1ment in Serdang Hospital. There were a total of 176 data were recorded in standardisedprofonna. Results: Out of 176 cases, majority 150 (85.2%) cases of infiltrating ductal carcinoma of breast were patient in age group below 65 years old. 60.8% of cases are Malay patient. MajOIity of cases were grade 2 (50.0%) followed by grade 3 (38.6%) and grade 1 (11.4%) tumour. The results of Chi-Square test shows that estrogen receptor (p=O.OO 1) . progesterone receptor (p=O.OO 1) and c-erbB2 receptor (p=O.019) expression were significantly associated with tumour histological grade. However, age group and ethnicity does not show association with expression of the those receptor, except for association of age and estrogen receptor (p=0.017) and association of ethnicity and progesterone receptor expression (p=0.004). Conclusion: Expression of estrogen receptor, progesterone receptor and C-erbB2 receptor was associated with the histological grade. There is also association between age and estrogen receptor expression and also between ethnicity and progesterone receptor expression. Keywords: Expression, Estrogen, Progesterone, C-erbB2, Receptor